The environmental constituents of eco-tourism in Jordan - Gharaybeh, Khlaif M (Faculty of Social Sciences and Humanities, UKM,Bangi, 2013)
Because of the growing universal importance of ecologically sustainable eco-tourism, and in line with the recommendation of the Stockholm Conference this research identifies and analyses the environmental components of tourism in Jordan. The objective is to discern the most significant environmental elements that constitute Jordan’s eco-tourism and how each of these elements shapes tourist attractions while managing ecological balance. To achieve this objective the researcher adopted an empirical and analytical approach by conducting field visits to identify the basics of the environment involved which was recorded in eighteen illustrations. Main findings of the study demonstrate that ecotourism crucially influences the future of Jordanian tourism as reflected by initiatives taken by the Jordanian Tourism Development Agency to promote Jordanian ecotourism all over the world especially through the Arab Gulf Union. In this vein the study puts forward several recommendations to enhance the ecological sustainability of Jordanian ecotourism including widening the reserve area between Alghor and the semi- Ghor mountains, and alleviating population pressures on the sites’ natural resources.